Postcards from London [videorecording (DVD)] - McLean, Steve; McLean, Steve; Dickinson, Harris, 1996-; Hauer-King, Jonah, 1995-; Cimadamore, Alessandro (Strand Releasing Home Video, 2019)
Follows the journey of a teenage boy who begins work as a high class male escort, but finds himself becoming an artists muse and art authenticator, complicated by a condition called Stendhal syndrome that causes him to faint when viewing fine art.